Zimbabwe w roku 2013 – nowe porządki w starym stylu? - Chołaszczyński, Krystian (Fides, Ratio et Patria. Studia Toruńskie, 2017)
The year 2013 seemed good for President Robert Gabriel Mugabe. After a period of dual power (2008-2013), he regained full control of Zimbabwe. The political opposition and the international community did not stand a chance with the president’s team. Interestingly, the fate of President Mugabe was determined by his own party and army, which for years served Crocodile faithfully. In 2017, the Mugabe era in Zimbabwe ended. However, in 2013 he was able to celebrate the full triumph. This article is about this.